Social Relations of Mathematics Education Students North Sumatra State Islamic University Medan with Sociometry Assisted - Abdurrahman; Indra Jaya; Muhammad Taufiq Azhari (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
Font paragraph this study aims to determine the level of social relations of mathematics education students with the help of sociometry. This research was revealed using sociometry tools. The population is staple 2018 second semester mathematics education students, totaling five classes. The sample used by mathematics class 2 researchers was 40 students. In this study produced several student positions at the level of social relations. In determining the level of one's social relations measured by assisted sociometry determined by a range of values from 0 to 1. So that the results of the level of social relations are obtained as follows: 1) 0.384 totaling 1 person, 2). 0.282 totaling 2 people, 3). 0.153 innumber, 4). 0.128 is 1 person, 5). 0.076 totaling 7 people, 6) 0.051 totaling 3 people, 7). 0.025 totaling 8 people, 8). 0 numbered 17 people. The conclusions of this study explain that there are still many social partners that must be improved, especially among individuals because student answers are quite varied.